Palladium complex embedded crosslinked polystyrene nanofibers as a green and efficient heterogeneous catalyst for coupling reactions. Issue 2 (24th August 2020) - Zhang, Benben; Ye, Zeyu; Qin, Min; Wang, Qingqing; Du, Yijun; Qi, Chenze; Shao, Linjun
Abstract: A simple and green chemical modification coupled with electrospinning technique has been developed to incorporate tetrakis(triphenylphosphine)palladium [Pd(PPh3 )4 ] inside crosslinked polystyrene nanofibers (Pd@CPS) as an efficient and stable heterogeneous palladium catalyst. The catalytic activities and recyclabilities of the prepared Pd@CPS catalyst have been evaluated by using Suzuki and Heck reactions of various aromatic halides separately with phenylboronic acid and alkenes. The Pd@CPS exhibited high‐catalytic activities for the Suzuki and Heck reactions of aromatic iodides to afford the products in excellent yields (coupling yields >88%). The catalytic activities and the nanofiber structure remained essentially unchanged even after recycling for five times. The high activities and stabilities of the prepared Pd@CPS catalyst can be attributed to the ultrafine fiber and embedment of palladium active species inside the nanofibers. Abstract :